2022
DOI: 10.1155/2022/6113352
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effect of Schisandrin on CORT-Induced PC12 Depression Cell Model by Inhibiting Cell Apoptosis In Vitro

Abstract: Background. In recent years, the incidence of depression is on the rise. Our paper proposed to study the protective effects of Schisandrin on CORT-induced PC12 depressive cell model and the underlying mechanisms. Methods. The in vitro models of PC12 were established using corticosterone (CORT). 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method was used to screen the effective concentration of Schisandrin, and the models of PC12 were treated with low, medium, and high concentrations of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Highly differentiated PC12 cells have the characteristics of typical neuroendocrine cells in morphology and function, so they are widely used in the study of depression [32]. For example, a model of PC12 cells damaged by a high concentration of CORT has been widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Highly differentiated PC12 cells have the characteristics of typical neuroendocrine cells in morphology and function, so they are widely used in the study of depression [32]. For example, a model of PC12 cells damaged by a high concentration of CORT has been widely used.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%